High density lipoprotein-cholesterol is inversely associated with blood eosinophil counts among asthmatic adults in the USA: NHANES 2011-2018 - Wen, Jun; Zhuang, Rongjuan; He, Chunyan; Giri, Mohan; Guo, Shuliang (Frontiers in Immunology, 2023)
(1) Background: A growing number of research strongly suggest that metabolic syndrome and dyslipidemia contribute to the establishment of a pro-inflammatory state in asthma, according to accumulating data. However, the majority of recent research has focused on the association between lipids and asthma in children and adolescents, with contradictory findings. Consequently, we analyzed the relationship between serum lipid and blood eosinophil counts using data from the NHANES in the USA. (2) Methods: After screening the individuals from the 2011 to 2018 NHANES survey, a total of 2,544 out of 39156 participants were eligible for our study. The potential association was discussed using the linear regression model, XGBoost algorithm model, generalized additive model, and two-piecewise linear regression model. In addition, we ran stratified analysis to identify specific demographics. (3) Results: After adjusting for covariates, the result indicated that blood eosinophil counts decreased by 45.68 (-68.56, -22.79) /uL for each additional unit of HDL-C (mmol/L). But serum LDL-C, total cholesterol or triglyceride was not correlated with blood eosinophil counts. Furthermore, we used machine learning of the XGBoost model to determine LDL-C, age, BMI, triglyceride, and HDL-C were the five most critical variables in the blood eosinophil counts. The generalized additive model and two-piecewise linear regression model are used to further identify linear relationship between the serum HDL-C and blood eosinophil counts. (4) Conclusions: Our study elucidated a negative and linear correlation between serum HDL-C and blood eosinophil counts among American asthmatic adults, suggesting that serum HDL-C levels may be associated with the immunological condition of asthmatic adults. There was no correlation between serum LDL-C, total cholesterol, or triglyceride levels and blood eosinophil counts.